Two Novel Three‐Dimensional Tetraphenylethylene‐Based Rare Earth MOFs with Ultra‐High Proton Conductivity and Performance Stability. Issue 60 (17th October 2022) - Wang, Shuyu; Zhao, Lijia; Sun, Hanxu; Wu, Yuanyuan; Wang, Ruidong; Zhang, Suoshu; Du, Lin; Zhao, Qi‐Hua
Abstract: Invited for the cover of this issue are the groups of Lin Du and Qi‐Hua Zhao at Yunnan University. The image depicts astronauts as protons moving along the hydrogen‐bond network in the channel of Eu‐ETTB/Gd‐ETTB. Read the full text of the article at 10.1002/chem.202202154 . Abstract : " The high proton conductivity values of Eu‐ETTB and Gd‐ETTB indicate the feasibility of designing new proton‐conducting materials based on the self‐assembly of specific organic ligands and metal ions ." This and more about the story behind the front cover can be found in the article at 10.1002/chem.202202154 ).